PROSES REHEATING BILLET DAN THIXOCASTING PADUAN Al-18Si BERSTRUKTUR NON-DENDRITIC - Suprihanto, Agus; Satrijo, Djoeli (ROTASI, 2007)
One of the important steps in semi-solid forming (SSF) especially thixoforming is the reheating process to achieve the required semisolid state of the billet. The reheating process is not only necessary to achieve the required semi-solid state of the billet, but also to control the microstructure of the billet. In the reheating process, billets are heated up to the temperature between the solidus and liquidus of the alloy to obtain accurately controlled solid fraction and spherical particles uniformly dispersed. The process variables such as reheating time, reheating temperature, reheating holding time, and induction heating power have much effects on the quality of the reheated billets. It is difficult to consider all the variables at the same time to predict the billet quality. In this paper, the process variables focused on reheating temperature and reheating holding time to see the correlation relationship between the process variables and the conditions of the billet quantitatively, and then simulate the thixocasting process to know the correlation relationship between the process variables and properties of the materials, which is the flow ability of the billet and the hardness of the thixocasting products. The alloys used in this experiment is non-dendritic Al-18Si alloy which formed used mechanical stirring method.